Is end-organ surveillance necessary in patients with well-functioning metal-on-metal hip resurfacings?: a cardiac MRI study. (May 2019) - Juneau, D.; Grammatopoulos, G.; Alzahrani, A.; Thornhill, R.; Inacio, J. R.; Dick, A.; Vogel, K. I.; Dobransky, J.; Beaulé, P. E.; Dwivedi, G.
Abstract : Aims: Cardiac magnetic resonance (CMR) was used to assess whether cardiac function or tissue composition was affected in patients with well-functioning metal-on-metal hip resurfacing arthroplasties (MoMHRA) when compared with a group of controls, and to assess if metal ion levels correlated with any of the functional or structural parameters studied. Patients and Methods: In all, 30 participants with no significant cardiac history were enrolled: 20 patients with well-functioning MoMHRA at mean follow-up of 8.3 years post-procedure (ten unilateral, ten bilateral; 17 men, three women) and a case-matched control group of ten non-MoM total hip arthroplasty patients (six men, four women). The mean age of the whole cohort (study group and controls) at the time of surgery was 50.6 years (41.0 to 64.0). Serum levels of cobalt and chromium were measured, and all patients underwent CMR imaging, including cine, T2* measurements, T1 and T2 mapping, late gadolinium enhancement, and strain measurements. Results: None of the MoMHRA patients showed clinically significant cardiac functional abnormality. The MoMHRA patients had larger indexed right and left end diastolic volumes (left ventricular (LV): 74 ml/m 2 vs 67 ml/m 2, p = 0.045; right ventricular: 80 ml/m 2 vs 71 ml/m 2, p = 0.02). There was a small decrease in T2 time in the MoMHRA patients (median 49 ms vs 54 ms; p = 0.0003). Higher metal ion levels were associated with larger LV volumes and with shorter T2 time. Conclusion: Although cardiac function is not clinically adversely affected in patients with well-functioning MoMHRA, modern imaging is able to demonstrate subtle changes in structure and function of the heart. As these changes correlate with systemic ion measurements, they may be consequences of wear debris deposition. Longer, longitudinal studies are necessary to determine whether cardiac function will become affected. Cite this article: Bone Joint J 2019;101-B:540–546.